POLICY AND IMPLEMENTATION OF EDUCATION MANAGEMENT BASED ON MADRASAH - Nana Meily Nurdiansyah; Hudriyah Hudriyah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to analyze policies from the socio-political scope as the basis for development in education in madrasah. Therefore, it goes on to say that this research was conducted through a descriptive qualitative approach to the type of library research, with the data source referring to literature data. The data analysis technique was carried out using content analysis, the scope of which consists of the depth of information content. The results showed that madrasah-based management is participatory management of madrasah by involving the principal, teachers, students, stakeholders, and the community to achieve the quality of education goals. The movement of education reform from centralization to decentralization abroad has been going on for 30 years, since 1960-1990. In Indonesia, constitutional reformation of education began to coincide with the reform era marked by the fall of the New Order in 1998. Education, which had been the matter of the central government, since the enactment of regional autonomy through Law number 22 of 1999 concerning Regional Government, was later amended by Law number 32 of the year. 2004, then the education affairs were handed over to the local government.